Aspects on the Promotion of Public-Private Partnership, in Romania, after 1990 - Florina Popa (Ovidius University Annals: Economic Sciences Series, 2019)
The introduction and expansion of market forces in the public sector field, as a result of substantial changes initiated by governments, as early as the first decades of the last century, has taken place based on some political mechanisms and institutional structures, whereat the Public-Private Partnership is included, too. In Romania, in the period after 1990, PPP has manifested itself in the context of the structural changes in the economy, in the period of transition, in the effort to find answer to the social and economic problems characteristic of the period. The paper shows the challenges in the Romanian economy generated by the transition from a model based on the command-control principle, to a competitive economy system, supported by the principle of freedom of action, as well as the applied strategies oriented towards the economic reform in the context of this process. There are shown the measures of upholding and promoting the cooperation between the public and the private sector through the actions of strengthening the legislative framework, respective, developing legal regulations and the establishment of institutional structures, with attributions in the implementation of the public-private partnership.